Analysis of the Selected Design Changes in a Wheel Hub Motor Electromagnetic Circuit on Motor Operating Parameters While Car Driving - Piotr Dukalski; Roman Krok (Energies)
The drive system of an electric car must meet road requirements related to overcoming obstacles and driving dynamics depending on the class and purpose of the vehicle. The driving dynamics of modern cars as well as size and weight limitations mean that wheel hub motors operate with relatively high current density and high power supply frequency, which may generate significant power losses in the windings and permanent magnets and increase their operating temperature. Designers of this type of motor often face the need to minimize the motor’s weight, as it constitutes the unsprung mass of the vehicle. Another limitation for motor designers is the motor dimensions, which are limited by the dimensions of the rim, the arrangement of suspension elements and the braking system. The article presents two directions in the design of wheel hub motors. The first one involves minimizing the length of the stator magnetic core, which allows for shortening of the axial dimension and mass of the motor but involves increasing the thermal load and the need for deeper de-excitation. The second one involves increasing the number of pairs of magnetic poles, which reduces the mass, increases the internal diameter of the motor and shortens the construction of the fronts, but is associated with an increase in the motor operating frequency and increased power losses. Additionally, increasing the number of pairs of magnetic poles is often associated with reducing the number of slots per pole and the phase for technological reasons, which in turn leads to a greater share of spatial harmonics of the magnetomotive force in the air gap and may lead to the generation of higher power losses and higher operating temperatures of permanent magnets. The analysis is based on a simulation of the motor operation, modeled on the basis of laboratory tests of the prototype, while the car is driving in various driving cycles.